2009
DOI: 10.1080/02688690902755605
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted peritoneal shunt insertion for hydrocephalus

Abstract: Over the past 50 years, various shunting procedures involving the peritoneum have been performed for the treatment of hydrocephalus. During placement of the peritoneal portion of the catheter, complications may arise secondary to a lack of direct visualization. We describe a reduced complication rate with laparoscopically-assisted placement of the peritoneal portion of the catheter. A retrospective chart review was performed of seventy-six (76) laparoscopically-assisted cases performed without consideration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Several studies have reported on the benefits and advantages of the laparoscopic insertion of the distal catheter in VPS placement since it was first introduced[7891016181920212223242526272829] and a few studies have compared aspects of the outcome and its impact on shunt survival in patients, who underwent VPS through laparoscopic technique and other traditional techniques used for distal catheter placement. [3141517303132333435]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the benefits and advantages of the laparoscopic insertion of the distal catheter in VPS placement since it was first introduced[7891016181920212223242526272829] and a few studies have compared aspects of the outcome and its impact on shunt survival in patients, who underwent VPS through laparoscopic technique and other traditional techniques used for distal catheter placement. [3141517303132333435]…”
Section: Discussionmentioning
confidence: 99%
“…Other series study reported mean operative time for the open shunt placement ranging from 40 to 130 min[31417213031323336] and for the laparoscopic technique 30-115 min,[314171920222530313233343536] but the definitions of surgical time differ somewhat in those reports. Certainly the operative time depends on patient and surgeon factors; obese patients, patients with a history of previous abdominal operation, or distorted abdominal anatomy require extra time when compared with other patients, since the abdominal surgeon often has to lyse adhesions in order to avoid malposition or obstruction of the distal catheter.…”
Section: Discussionmentioning
confidence: 99%
“…According to the author's knowledge, a ventriculo-peritoneal shunting procedure with laparoscopically controlled insertion of the catheter into the abdominal cavity has not been described to date in dogs. The advantages of laparoscopy-assisted ventriculo-peritoneal shunting include full control over catheter placement in the abdominal cavity which minimizes the risk of damage to the intestines and other abdominal organs (Sekula et al, 2009). Laparoscopically-assisted placement of the catheter tip into the liver area also minimizes the likelihood of catheter obstruction which may be caused by omental or intestinal wrapping around the walls and the openings of the catheter (Argo et al, 2009;Sekula et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of laparoscopy-assisted ventriculo-peritoneal shunting include full control over catheter placement in the abdominal cavity which minimizes the risk of damage to the intestines and other abdominal organs (Sekula et al, 2009). Laparoscopically-assisted placement of the catheter tip into the liver area also minimizes the likelihood of catheter obstruction which may be caused by omental or intestinal wrapping around the walls and the openings of the catheter (Argo et al, 2009;Sekula et al, 2009). One major disadvantage of laparoscopic procedures is the equipment cost and the requirement for some experience with laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors 1,2,4,[9][10][11] have introduced new methods to improve shunt placement, especially by using laparoscopy for placement of the peritoneal catheter. The use of laparoscopy in VP shunt placement has led to a reduction in operating time, blood loss, and infection while maintaining shunt viability.…”
mentioning
confidence: 99%